Inflammatory Myofibroblastic Tumor of the Urinary Bladder: A Case Report - Etani, Toshiki (Case Rep Oncol, 2016)
An inflammatory myofibroblastic tumor (IMT) is a distinctive neoplasm composed of myofibroblastic and fibroblastic spindle cells, accompanied by inflammatory infiltration of plasma cells, lymphocytes, and eosinophils. IMTs rarely occur in the urinary bladder. It is important to distinguish this tumor from other malignant spindle cell tumors. Herein, we report a patient with an IMT showing muscle invasion, who underwent a transurethral resection of the bladder tumor and, at a later date, partial cystectomy. The resected tumor specimen revealed a proliferation of spindle-shaped cells on a background of plasma cells and lymphocytes. Immunohistochemical staining showed the tumor to be positive for anaplastic lymphoma kinase (ALK), smooth muscle actin, and vascular endothelial growth factor (VEGF). Such histopathological findings were indicative of an IMT, suggesting the use of inhibitors of ALK and VEGF as pharmacotherapy.